ISOLATION AND CHARACTERISTICS OF PHOSPHATE SOLUBILZING BACTERIA (PSB) FROM VEGETATIVE AND GENERATIVE PHASE OF MAIZE RHIZOSPHERE - Fany Juliarti Panjaitan (JURNAL AGROPLASMA, 2020)
The plants acquire phosporus from soil solution as phosphate anion. The availability of nutrients is very low in soil and crops compared to the other macronutriens. It precipitates in soil as orthophosphate or absorbed by Al and Fe so that inhibiting the plant growth. Phosphate solubilizing bacteria are able to release the P bond of clay minerals and provide it for crops. The research aimed to get phosphate solubilzing microbes from maize (Zea mays L.) rhizosphere. The soil samples were taken from the maize rhizosphere in both the vegetative and generative phases in the Cikabayan Bogor experimental farm. The phosphate solubilzing bacteria were determined for its ability to dissolve phosphate in liquid Pikovskaya media. The results of research were obtained 16 phosphate solubilizing bacteria, each of the 12 isolates derived from maize rhizosphere in vegetative phase (JM FIO) and 4 isolates in generative phase (JT FIO). The phosphate solubiliton index of each phosphate solubilizing bacteria was varied, namely 2,2-4, the largest dissolution index obtained at JM FIO 1. The largest phosphate dissolving ability in liquid Pikovskaya media was showed by JM FIO 3 isolate, P value was 0,60 ppm or increased 300% of control then followed by JM FIO 9 with 0,43 ppm P. The research also showed that JM FIO 3 and JM FIO 9 were not pathogenic and potentially could be used as biological fertilizer with number of cells at each 4.2 x 109 and 1.2 x 109 CFU/g of carrier.Key Words : Phosphate Solubilizing Microbe, Maize, Rhizosphere